In Reference to “Bibliometric Analysis of Research Trends on Acupuncture for Neck Pain Treatment Over the Past 20 Years”[Letter] - Dong Q (Dove Medical Press, 2021)
Qunya Dong,1,* Wenzhe Wu2,* 1Zhejiang Rehabilitation Medical Center, Hangzhou City, Zhejiang Province, People’s Republic of China; 2The Third Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou City, Zhejiang Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wenzhe WuThe Third Affiliated Hospital of Zhejiang Chinese Medical University, No. 219 Moganshan Road, Hangzhou City, Zhejiang Province, People’s Republic of ChinaEmail wuwenzhe_zcmu@163.com View the original paper by Dr Park and colleagues